2023
DOI: 10.3389/fgene.2023.1248544
|View full text |Cite
|
Sign up to set email alerts
|

Combination of trio-based whole exome sequencing and optical genome mapping reveals a cryptic balanced translocation that causes unbalanced chromosomal rearrangements in a family with multiple anomalies

Min Xie,
Jiangyang Xue,
Yuxin Zhang
et al.

Abstract: Background: Balanced translocation (BT) carriers can produce imbalanced gametes and experience recurrent spontaneous abortions (RSAs) and even give birth to a child with complex chromosomal disorders. Here, we report a cryptic BT, t(5; 6) (p15.31; p25.1), in the proband’s grandmother, which caused unbalanced chromosomal rearrangements and various anomalies in the two subsequent generations. We also provide a thorough overview of the application of optical genome mapping (OGM) to identify chromosomal structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…At the same time, OGM also revealed that the proband's grandmother had a balanced translocation that caused multiple malformations in the subsequent two generations. 29 These case reports have shown that OGM has technical advantages in identifying SVs. However, the high cost of OGM currently limits its widespread application.…”
mentioning
confidence: 98%
“…At the same time, OGM also revealed that the proband's grandmother had a balanced translocation that caused multiple malformations in the subsequent two generations. 29 These case reports have shown that OGM has technical advantages in identifying SVs. However, the high cost of OGM currently limits its widespread application.…”
mentioning
confidence: 98%